Investigation of the feed resource for buffalo - Ivanova, Silviya; Markov, Nikolay (Acta Scientiarum. Animal Sciences, 2021)
Buffaloes make better use of coarse and inferior feed by converting them to biologically valuable animal production. They make very good use of the additional production of crop production, such as straw, sunflower cakes, sprouts and other. The aim is to study the physicochemical and fatty acid composition of the rations of buffalo of the Bulgarian mura breed in a church farm in Gigentsi village, Pernik District. The application of standard methods for the nutrition of buffaloes in separate periods - pastured with succulent fodder, winter (indoor) with coarse fodder, through which the ruminants are provided with the necessary nutritional components, allows to obtain high quality milk as a basic raw material for the production of dairy products. The use of succulent fodder and the incorporation of root crops into the feed instead of the buffalo concentrate provides them with respect to linoleic and alphalinolenic fatty acids, which are substrates for the synthesis of CLA (anticancer action) in rumen of ruminants.